KAJIAN TENTANG KOTA BERKELANJUTAN DI INDONESIA (STUDI KASUS KOTA YOGYAKARTA) - Ervianto, Wulfram Indri (Media Teknik Sipil, 2018)
AbstractSustainability issues have become popular, these are caused by a global warming phenomenon that may concern the survival of life on the Earth by marking the increasing Earth’s average temperature caused by the greenhouse effect. The purpose of this study is to find out how the city of Yogyakarta accomodates the principles of eco-friendly approaches. The using of research methodology is based on qualitative approaches by interpreting of secondary data. Several achievements of sustainability which are (a) The increasing of Yogyakarta’s temperature and humidity is relatively high, one of  the effect is the lack of green open spaces, ± 17,98%. (b) In the case of air pollution issues indicate the level of carbon dioxide is 559.54 ppm exceeding the threshold applied by World Bank (381 PPM). (c) The inequality of income distribution indicates at the moderate imbalance (0,51). The result of this study are as follows : (a) To implement the concept of sustainable city. (b) To evaluate the environmental impact assessments for infrastructure in Yogyakarta. (c) To Issuie mayoral regulations requiring every infrastructure must have facility for treating hazardous and toxic waste materials independently and reporting periodic and routine audit results. (d) To develop appropriate technology for the processing of wastewater at the village level in order to be used for other purposes. (e) To enable economic activity at the village situation.Keywords: Study, Sustainable City, IndonesiaAbstrakIsu keberlanjutan menjadi populer, pemicunya adalah fenomena pemanasan global yang mengkawatirkan keberlangsungan kehidupan di Bumi. Gejalanya adalah meningkatnya suhu rata-rata di Bumi yang disebabkan oleh efek gas rumah kaca. Tujuan kajian adalah untuk mengetahui capaian kota Yogyakarta telah mengakomodasi prinsip ramah lingkungan. Metodologi penelitian yang digunakan didasarkan pada pendekatan kualitatif melalui interpertasi data sekunder yang tersedia dan dapat diakses oleh umum. Beberapa capaian keberlanjutan di kota Yogyakarta adalah: (a) Suhu dan kelembaban kota Yogyakarta mengalami peningkatan relatif tinggi, disebabkan karena terbatasnya ruang terbuka hijau, yaitu ±17,98%. (b) Pencemaran udara, kadar  sebesar ±559,54 PPM melebihi ambang batas yang ditetapkan oleh World Bank, yaitu 381 PPM. (c) Rasio gini pada ketimpangan moderat (0,451). Hasil kajian adalah : (a) Mengimplementasikan konsep kota berkelanjutan secara lengkap dan benar. (b) Mengevaluasi analisis dampak lingkungan untuk hotel, pusat perbelanjaan, dan fasilitas kesehatan di kota Yogyakarta. (c) Menerbitkan peraturan walikota yang mewajibkan setiap hotel, pusat perbelanjaan, dan fasilitas kesehatan memiliki fasilitas pengolahan limbah bahan berbahaya dan beracun secara mandiri dan melaporkan hasil audit secara berkala dan rutin. (d) Mengembangkan teknologi tepat guna untuk pengolahan limbah cair di tingkat kampung. (e) Menghidupkan aktivitas ekonomi di tingkat kampung.Kata kunci: Kajian, Kota Berkelanjutan, Indonesia.